c-Myc-PD-L1 Axis Sustained Gemcitabine-Resistance in Pancreatic Cancer - Yao, Jingjing; Huang, Min; Shen, Qinghong; Ding, Ming; Yu, Shaofang; Guo, Yajuan; Lin, Yuefang; Zheng, Yaqiu; Chen, Wenbo; Yan, Wenxin; Liu, Zhongqiu; Wang, Dawei; et al. (Frontiers in Pharmacology, 2022)
Pancreatic cancer ranks fourth among cancer-related deaths, with a 5-year overall survival rate being below 10%. Gemcitabine (dFdC) has been considered the first-line drug for patients with pancreatic cancer. However, the clinical effectiveness is less than 20% due to drug resistance. Most importantly, overwhelming evidence suggested c-Myc and PD-L1 were generally highly expressed in pancreatic cancer patients. However, whether dFdC-resistant pancreatic cancer is associated with c-Myc and PD-L1 has not been elucidated. In our present study, we found that the expression of c-Myc and PD-L1 was markedly increased in pancreatic tumor tissues compared with adjacent tissues. Similarly, c-Myc and PD-L1 expression were also remarkably elevated in dFdC-resistant Panc-1 cells compared with parental cells. In addition, dFdC sensitivity was enhanced by the combination of dFdC and c-Myc inhibitors in Panc-1 cells. Interestingly, its sensitivity was reduced when c-Myc was overexpressed. Moreover, PD-L1 protein expression was dramatically down-regulated when treated with c-Myc inhibitors. Furthermore, artesunate (ARTS) screened from 18 compounds could reverse dFdC resistance in combination with dFdC in dFdC-resistant Panc-1 cells in vitro and suppressed DMBA-induced pancreatic cancer in vivo. In summary, our data revealed that the mechanism of dFdC resistance may be that c-Myc overexpression contributed to increased PD-L1 expression, and ARTS could overcome dFdC-resistant pancreatic cancer by inhibiting c-Myc and PD-L1. Our findings not only suggest c-Myc and PD-L1 as novel prognostic biomarkers in dFdC-resistant pancreatic cancer, but also provide ARTS as a promising candidate for overcoming dFdC resistance.